Peran Kepala Sekolah Sebagai Leader Dalam Meningkatkan Kompetensi Profesional Guru di SMK Negeri 1 Siborongborong - Juni Persatuan Hrefa; Senida Harefa; Abai Manupak Tambunan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The aim of this research is to determine the role of the school principal as a leader in enhancing the professional competence of teachers at SMK Negeri 1 Siborongborong. The method employed in this research is descriptive qualitative research. Data collection was conducted through observation, interviews, and documentation. The subjects of this study were the school principal and teachers. Data analysis techniques included data reduction, data presentation, and drawing conclusions. The findings of this research describe the role of the school principal as a leader in improving the professional competence of teachers at SMK Negeri 1 Siborongborong. The roles of the school principal as a leader involve providing guidance and supervision to all educators by holding joint meetings, enhancing the willingness and capabilities of educational staff through specific evaluations conducted three times a year to enhance the professional competence of teachers, establishing two-way communication by engaging in regular communication with all educators almost every day, and delegating tasks to all educators and educational staff, such as carrying out learning evaluations for all teachers, students, and all personnel serving at SMK Negeri 1 Siborongborong with the aim of enhancing the professional competence of teachers.